Nephrotic Syndrome due to Focal Segmental Glomerulosclerosis Complicating Sjögren's Syndrome: A Case Report and Literature Review. (15th August 2019) - Kurihara, Shigekazu; Harada, Makoto; Ichikawa, Tohru; Ehara, Takashi; Kobayashi, Mamoru
Abstract : Background . Renal tubular acidosis and tubulointerstitial nephritis constitute the primary renal complications associated with Sjögren's syndrome (SjS), and glomerulonephritis and nephrotic syndrome are rare. Case Presentation . A 79-year-old Japanese woman presented with bilateral leg edema and weight gain and was diagnosed with nephrotic syndrome. In addition, she reported a 5-year history of dryness of mouth and was diagnosed with SjS. Renal biopsy revealed segmental glomerulosclerosis, with some specimens showing collapse of the glomerular capillary loops, proliferation of glomerular epithelial cells, and sclerotic lesions at the tubular poles, without spike formation, double contour lesions, or any other changes of the glomerular basement membrane. Immunofluorescence staining showed no immune complex (immunoglobulin IgG, IgA, or IgM) or complement (C3) deposition in the glomerular capillary walls. Based on these findings, she was diagnosed with focal segmental glomerulosclerosis (FSGS). The administration of steroid and cyclosporine achieved complete remission of nephrotic syndrome. Conclusion . Although glomerular diseases are rare, a variety of glomerular lesions including FSGS are reported in patients with SjS. Therefore, renal biopsy is warranted in patients with SjS presenting with severe urinary abnormalities.